World experience of circular economy implementation and prospects for Ukraine - Pavlikha, Nataliia; Korneliuk, Olha (Polskie Towarzystwo Ekonomiczne Oddział w Poznaniu, 2022)
The essence and principles of circular economy are studied, the advantages of the introduction of circular economy are analyzed; features of functioning of circular business models; the development of the circular economy in the countries of the European Union is studied, the prospects of introduction of the closed-cycle economy are substantiated, the influence of COVID-19 on the prospects of the circular economy development is analyzed. The advantages of the circular economy are analyzed taking into account the need to adapt to the new conditions caused by the COVID-19 pandemic.
Keywords: circular economy; circular business model; sustainable development; resource efficiency; growth strategy